2020
DOI: 10.21203/rs.2.14059/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic analysis reveals hub genes and subnetworks related to ROS metabolism in Hylocereus undatus through novel superoxide scavenger trypsin treatment during storage

Abstract: Background: It was demonstrated in our previous research that trypsin scavenges superoxide anions. In this study, the mechanisms of storage quality improvement by trypsin were evaluated in H. undatus. Results: Trypsin significantly delayed the weight loss and decreased the levels of ROS and membrane lipid peroxidation. Transcriptome profiles of H. undatus treated with trypsin revealed the pathways and regulatory mechanisms of ROS genes that were up- or downregulated following trypsin treatment by gene ontology… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our laboratory found that trypsin has a good fresh‐keeping effect on H. undatus . It can regulate the level of endogenous reactive oxygen species (ROS) in H. undatus peels (Li et al, 2019, 2020; Pang et al, 2020) and inhibit the level of saturated fatty acids (Li et al, 2022; Pang et al, 2022), induce the stoma closure (Li, Li, et al, 2021), and the biosynthesis of related substances in phenylpropanoid pathways such as lignin, chlorogenic acid (Li, Zhang, et al, 2021), and flavonoids (Pang et al, 2021). It can also affect the free radical scavenging activity of flavonoids, such as DPPH and ABTS (Li et al, 2014, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory found that trypsin has a good fresh‐keeping effect on H. undatus . It can regulate the level of endogenous reactive oxygen species (ROS) in H. undatus peels (Li et al, 2019, 2020; Pang et al, 2020) and inhibit the level of saturated fatty acids (Li et al, 2022; Pang et al, 2022), induce the stoma closure (Li, Li, et al, 2021), and the biosynthesis of related substances in phenylpropanoid pathways such as lignin, chlorogenic acid (Li, Zhang, et al, 2021), and flavonoids (Pang et al, 2021). It can also affect the free radical scavenging activity of flavonoids, such as DPPH and ABTS (Li et al, 2014, 2018).…”
Section: Introductionmentioning
confidence: 99%